Achieving Longevity in Wireless Body Area Network by Efficient Transmission Power Control for IoMT Applications - G., Rajesh; X, Mercilin Raajini; N., Kritika; A, Kavinkumar; K, Martin Sagayam; Abd Wahab, Mohd Helmy; Md. Som, Mohamad (International Journal of Integrated Engineering, 2022)
The application of tiny body sensors to collect, process, store, analyze, and retrieve medical information from a human body is a part of the Internet of Medical Things (IoMT). IoMT helps to monitor and track human vital health parameters, predict disease, notify the patients and the health care professionals with relevant data for analyzing the problems before they become severe and for earlier invention. By 2022, more than 60 % of IoT applications will be health-related. The convergence of biomedical sensors, wireless body area networks (WBAN), Information technology, and bioinformatics will help improve the efficiency of saving human lives. In a WBAN, network longevity is challenging because of the limited supply of low power battery energy in tiny body sensor nodes. Here, we proposed an energy-efficient transmission power control (TPC) algorithm to extend the network lifetime in IoMT networks for healthcare applications by eliminating the transceiver overhearing problem. In TPC, human tissue resistivity properties are considered to adjust the transmission power, which reduces the communication power and extends the network lifetime. The simulation results show that network power consumption is reduced by 35%.